Entre le changement et l'indiscipline - Roy, Jean-Louis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In this article the author presents a view on federal-provincial relations which he sees as characterized by constant change and a lack of discipline both of which have recently resulted in a degradation of the system itself. Hence, there is a need to return to a reasonable level of predictability in federal-provincial relations which may be characterized by moderation. Roy points out that English Canada and Quebec are not mutually exclusive societies and there exists a variety of mechanisms which could contribute to common understanding. As publisher of the daily « Le Devoir », Roy points out that his paper was staunchly opposed to the Constitutional Law of 1982. Yet, due to the majority of Quebecers who rejected the sovereignty option as well as the recent ruling on a veto prerogative for Quebec, a new outlook must be adopted. Quebec must ask itself three questions. First, has it given sufficient consideration to the existence of its various partners ? Secondly, could Quebec be moving too fast towards its goals ? Thirdly, has Quebec capitalized on all the positive elements in its relationships ? The author concludes by affirming that regardless of other elements, Quebec and Canada have the obligation to negotiate with their neighbors